PENERAPAN MODEL PROBLEM BASED LEARNING BERMUATAN GAMIFICATION UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI OPERASI HITUNG BILANGAN PECAHAN - Muhamad Adrian; Elly Sukmanasa; Epon Nurlaela (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to improve mathematics learning outcomes in the operational material for calculating fractions in grade of SDN Julang, Bogor City, consisting of 25 students using a problem based learning model containing gamification. This type of research is classroom action research. The data collection techniques used were observation and tests, then the data obtained was analyzed quantitatively descriptively. The results of this research were that at the pre-cycle stage the percentage of classical completion was 44%, then increased in first cycle to 68% and increased again in cycle II to 92%. The average class score increased, which in the pre-cycle was 58.4, then increased in the second cycle to 74.8 and increased again to 85.6 in the second cycle. Based on the research results, it was concluded that the use of a problem based learning model containing gamification can improve mathematics learning outcomes in fractional counting operation material.